Wired Research: The Accessibility of Electronic Journals in Science and Technology, January 11, 1998 - Chad E. Buckley; Amy Prendergast (Issues in Science and Technology Librarianship)
Linda Sacks gave a brief history and description of Elsevier's new web-based ScienceDirect electronic journal product. Barbara Lange described IEEE's new electronic journal product called IEL (IEEE/IEE Electronic Library). A question and answer period followed. Discussion focused on pricing issues, subscribing to specific titles rather than an entire collection of titles, and linking from online indexes directly to full text electronic journals.